2017
DOI: 10.1080/15287394.2017.1357307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green juice and their bioactive compounds on genotoxicity induced by alkylating agents in mice

Abstract: Kale juice (Brassica oleracea L. var. acephala D.C.) is a reliable source of dietary carotenoids and typically contains the highest concentrations of lutein (LT) and beta-carotene (BC) among green leafy vegetables. As a result of their antioxidant properties, dietary carotenoids are postulated to decrease the risk of disease occurrence, particularly certain cancers. The present study aimed to (1) examine the genotoxic and antigenotoxic activity of natural and commercially available juices derived from Brassica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Epidemiological studies have shown an interactive association between dietary habits, lifestyle and genetics with the increased risk of many different chronic diseases, including cancer. The most consistent finding regarding diet as a determinant of cancer risk prevention is the relationship between consumption of vegetables and fruits and reduced risk of several types of cancers (Ben et al 2015;Fagundes et al 2017;Kok et al 2010;Oliveira De Quadros et al 2017;Venancio et al 2016). Knowledge of the relationship between diet and cancer has advanced in recent years, but much remains to be elucidated with respect to diet and dietary components in cancer prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown an interactive association between dietary habits, lifestyle and genetics with the increased risk of many different chronic diseases, including cancer. The most consistent finding regarding diet as a determinant of cancer risk prevention is the relationship between consumption of vegetables and fruits and reduced risk of several types of cancers (Ben et al 2015;Fagundes et al 2017;Kok et al 2010;Oliveira De Quadros et al 2017;Venancio et al 2016). Knowledge of the relationship between diet and cancer has advanced in recent years, but much remains to be elucidated with respect to diet and dietary components in cancer prevention.…”
Section: Introductionmentioning
confidence: 99%
“…26 The effects of confounding factors such as diet, exposure to cigarette smoke, place of residence, age, and occupation of the father and mother are among other parameters that may be responsible for the existing controversy in the literature. 7,[14][15][16][17]21,27 In this study, demographic information of patients was collected to control for the confounding factors as much as possible. Some previous studies assessed the effect of confounders in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…27 Also, Fagundes et al evaluated the effect of beta-carotene and showed that carotenoids have protective effects and can repair the damaged DNA. 16 In such studies, since each patient serves as his/her own control, the changes after 10 days are attributed to X-ray exposure. 28 The cytotoxicity and genotoxicity of other radiographic modalities have also been evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation